Kedudukan Dan Hak Mewaris Anak Dari Anak Angkat Seorang Pradana Dalam Hukum Waris Adat Bali - Rata, Kd Dewantara (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p15, 2021)
The people in Bali adhere to the patrilineal kinship system by drawing the lineage of men, hence the son or adopted son, maupu daughter or daughter who changed his status as sentana rajeg as purusa entitled to the inheritance of the heir. It is only in society that the issue of heirs arises regarding the return of a married daughter and re-entry into her original family, whereas in her original family there is a legitimate heir from the heir. The research method in this journal, using normative research specifications, is to provide the most thorough source of human beings, circumstances or other symptoms. The approach used is normative, which is a method that focuses on research into secondary data in the form of primier legal materials, secondary legal materials and tertiary legal materials. The collection of sources of legal materials used in this journal is the study of literature documents and legal journals. Based on the research conducted, that the son of an adopted child of a pradana who enters and lives in his family without going through balinese traditional ceremonies is associated with the customary inheritance law of a position not as an heir from the heir so that it has no right to inherit the inheritance of the heir. Therefore, a prefunder and his offspring will have the same obligation as the heir, while his right is only granted on the basis of volunteering by the rightful heir of the heir.